2011
DOI: 10.1109/twc.2011.072511.101661
|View full text |Cite
|
Sign up to set email alerts
|

CoMP-CSB for ICI Nulling with User Selection

Abstract: The capacity of downlink multiple-input multipleoutput (MIMO) cellular networks is significantly limited by intercell interference (ICI), particularly at cell boundaries. Recently, two types of coordinated multiple point transmission (CoMP) technologies, joint processing and transmission (JPT) and coordinated scheduling and beamforming (CSB), were proposed. These technologies are intended for the latest cellular communication standard in order to improve the performance of cell-edge users who suffer from signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…The authors in [5] brought some practical techniques to overcome the fundamental requirements of CoMP-JT. In addition, field trial results of [2,[9][10][11] have confirmed the advantages of applying CoMP in practical systems. So in this paper, these preliminaries are assumed to be provided.…”
Section: Background and Related Workmentioning
confidence: 70%
“…The authors in [5] brought some practical techniques to overcome the fundamental requirements of CoMP-JT. In addition, field trial results of [2,[9][10][11] have confirmed the advantages of applying CoMP in practical systems. So in this paper, these preliminaries are assumed to be provided.…”
Section: Background and Related Workmentioning
confidence: 70%
“…With respect to the scenario depicted in Fig. 2, this means that information about the complex channel transfer functions H 11 , H 21 , H 12 and H 22 is required, which in addition has to be shared between BSs [4]. To obtain full CSI, in time division duplex (TDD) systems, channel reciprocity can be utilized, such that detailed CSI for the downlink can be obtained through uplink channel estimation [22].…”
Section: Channel State Informationmentioning
confidence: 99%
“…Coordinated beamforming means that the BSs coordinate the beams they create (normally by means of precoding) in such a way that they do not produce interference to an MS of a neighbouring BS. The coordination schemes especially differ in the amount of data that needs to be exchanged between the BSs [4]. The tighter the cooperation is, the higher the requirements in terms of latency and bandwidth are.…”
Section: Introductionmentioning
confidence: 99%
“…Based Wyner secret eavesdropping channel capacity [13][14][15] is defined as the guarantee perfect secrecy (perfect secrecy) under the premise of the system up to the maximum transmission rate.…”
Section: ) Spread Spectrum and Frequency Hopping Encryption Technologymentioning
confidence: 99%